SOSIALISASI PELATIHAN DAN PENDAMPINGAN PELAKU USAHA UMKM DI DESA KEBUN PISANG KABUPATEN TAPANULI TENGAH - Hendra Sahputra; Mhd Shafwan Koto (COVIT (Community Service of Health), 2022)
Community service activities by universities must always be directed at activities that have an impact and benefit directly felt by the user community and have an orientation that is directed at solving problems faced by the community as well as directed at efforts to foster MSME business actors in order to improve the quality of the community's economy. This method of implementing Community Service (PKM) activities is a combination of financial bookkeeping training and socialization and understanding of the process of utilizing KUR funds in banking for MSME business actors in Kebun Pisang Village, Badiri District, Central Tapanuli Regency. This activity is expected to be able to increase understanding of the company actors who are present in micro and small, which have a simple place of business, and have weaknesses in simple financial records without an entry date and the company will slowly lose money. The results of this activity are expected to contribute ideas about knowledge and skills in maintaining or opening new businesses/businesses and increasing profits so that existing businesses can further develop by finding solutions in capital, namely by bringing together MSME business actors with investors in this case. banks to invest in the form of offering KUR loan funds for MSME business actors in Kebun Pisang Village. Keywords: Socialization of Training and Mentoring, Bookkeeping, KUR Dana Fund